Teologi Raputallang: Sebuah Konstruksi Teologi Lokal dengan Perspektif Robert J. Schreiter atas Hermeneutika Galatia 6:2 sebagai Dasar Rekonsiliasi Konflik dalam Gereja - Rerung, Alvary Exan (Tumou Tou, 2023)
The reality of the Church as a community that cannot avoid conflict or dispute is something that cannot be denied. Church communities in which there are differences in economics, backgrounds, education, parenting patterns, and so on, will continue to be the trigger for conflicts or disputes within the Church. If this is not taken seriously, then any conflict or dispute will have the potential to divide a community, such as the Church. Seeing this reality, this paper uses a qualitative approach to create a local theology, namely the theology of raputalang by using the lens (perspective) of the local theology design offered by Robert J. Schreiter. This study also uses the reading of the text of Galatians 6:2, to assist the theology of raputalang in achieving what this research wants, namely as a basis for reconciliation of conflicts in the Church. With that description, this paper will offer how everyone should behave towards each other so that it is not easy to cause conflicts or disputes in their coexistence. This will make the Church more likely to avoid conflicts or disputes and be able to focus on proclaiming peace to all creatures, as God has commanded.